Implementasi Kebijakan Mitigasi Bencana Banjir di Nagari Sicincin - Aulia Maulani, Thalita; Syamsir, Syamsir (PUBLICNESS: Journal of Public Administration Studies, 2024)
This research aims to review the implementation of flood mitigation policies in Nagari Sicincin, which is often affected by floods due to poor drainage, waste accumulation, and low public awareness in maintaining environmental cleanliness. The mitigation policy from the Water Resources and Construction Service of West Sumatra Province focuses on improving irrigation infrastructure. This research uses a descriptive qualitative method with purposive sampling to select informants. Data is collected through observation, interview, and documentation study, data validity is tested with triangulation technique, and data analysis is done through the process of data reduction, data presentation, and drawing conclusions. The research results show that even though the infrastructure development has been running, but the flood is still hitting Nagari Sicincin and the construction of the infrastructure has not been completed due to lack of budget and difficulties in providing land. In addition, non-structural aspects such as public education have not been maximized. Poor inter-institutional coordination as well as limited human and financial resources slow down policy implementation.